IN VITRO METHANE PRODUCTION OF ERAGROSTIS HAY TREATED WITH GRADED LEVELS OF UREA OR NITRATE - F. A. Adejoro; A. Hassen (Journal of Animal and Plant Sciences, 2018)
Urea treatment of protein deficient feeds serve as a source of ammonia nitrogen supply for rumen fermentation. This study was undertaken with the objective of determining the effect of treating Eragrostis curvula hay with varying levels of urea or nitrate on digestibility and in vitro fermentation. Grass hay was sprayed with urea solution at 0.5%, 1.0%, and 1.5% DM and calcium nitrate was used as a replacement of urea on an iso-nitrogenous basis. This was followed by 30 days anaerobic storage in airtight bottles with each treatment having three replicates. Following anaerobic treatment, hay samples were dried, milled and evaluated for their chemical composition, in vitro organic matter digestibility, and in vitro fermentation and methane production. Feed treatment with both urea and nitrate reduced ADF content of hay, while crude protein content was increased. In vitro organic matter digestibility of treated hays increased with inclusion levels although urea recorded higher values than nitrate. Nitrate treatment significantly reduced in vitro methane by 14-33% while there was no significant methane reduction in the urea treated diets. Total volatile fatty acid, ammonia N and pH across treatments were statistically not different (P>0.05). While urea treatment seems to improve digestibility better, it did not confer additional benefits when compared to nitrate treatment that provided the additional benefit of methane reduction with an acceptable level of improvement in feed digestion and fermentation. Nitrate can thus be incorporated into feed treatment to improve the nutritional value of poor quality hays. fungicide (Oji et al. 2007). Non-protein nitrogen (NPN)
Keywords: ammoniation; digestibility; Eragrostis hay; nitrate; methane emission.